Breast Adipocyte Co-culture Increases the Expression of Pro-angiogenic Factors in Macrophages - Yadav, Nalini V. S.; Barcikowski, Arthur; Uehana, Yuko; Jacobs, Aaron T.; Connelly, Linda (Frontiers in Oncology, 2020)
Obese individuals with breast cancer have a poorer prognosis and higher risk of metastatic disease vs. non-obese patients. Adipose tissue in obese individuals is characterized by an enhanced macrophage infiltration, creating a microenvironment that favors tumor progression. Here, we demonstrate a role for adipocyte-macrophage interactions in the regulation of angiogenesis. Co-culture of THP-1 macrophages with human breast adipocytes led to increased expression of the pro-angiogenic growth factor, vascular endothelial growth factor A (VEGFA). Several adipocyte-derived proteins including leptin, insulin, IL-6, and TNF-alpha were each capable of increasing VEGFA expression in THP-1 macrophages, identifying these as possible mediators of the changes that were observed with co-culture. Furthermore, analysis of THP-1 culture media by antibody array revealed that THP-1 secrete several other pro-angiogenic signals in response to adipocyte co-culture, including interleukin 8 (IL-8), matrix metalloproteinase 9 (MMP9), pentraxin 3 (PTX3), and serpin E1 (plasminogen activator inhibitor 1, PAI1) after co-culture with human adipocytes. We used an in vitro endothelial tube formation assay with human vascular endothelial cells to evaluate the effects of THP-1 culture media on angiogenesis. Here, culture media from THP-1 cells previously exposed to human adipocytes stimulated endothelial tube formation more significantly than THP-1 cells cultured alone. In summary, we find that adipocyte co-culture stimulates the expression of pro-angiogenic mediators in macrophages and has pro-angiogenic effects in vitro, thus representing a possible mechanism for the enhanced risk of breast cancer progression in obese individuals.